Effect of peppermint essential oil (Mentha piperita L.) in migraine-like responses in female rats - Koren, Laura de Oliveira; Lejeune, Vanessa Bordenowsky Pereira; Baggio, Darciane Favero; Luz, Fernanda Mariano Ribeiro da; Geremias Chichorro, Juliana (Headache Medicine, 2024)
Migraine is a severe and disabling neurological disorder characterized by headache, photophobia, phonophobia, nausea and vomiting. It is considered the top cause of years lived with disability between the ages of 15–49, being two to three times more common in women than in men. Pharmacological treatment of migraine has advanced in the past years but is still considered unsatisfactory for a significant number of patients. There is growing evidence that essential oils may provide benefit for migraineurs. Herein it was tested the hypothesis that peppermint essential oil (Mentha piperita L.) could reduce migraine-related responses in rats. The model consisted in the injection of calcitonin-gene-related peptide (CGRP) in the trigeminal ganglion (TG) of female rats to induce the development of immediate periorbital cutaneous allodynia and late photosensitivity (24 h after CGRP). Inhalation of the peppermint essential oil during 15 minutes before CGRP injection in the TG did not reduce periorbital allodynia and photosensitivity of female rats. However, when the exposure occurred after CGRP injection, peppermint essential oil caused a significant reduction in both parameters. Likewise, intranasal application of menthol, a major component of peppermint essential oil caused a significant reduction of periorbital allodynia induced by CGRP. In conclusion, peppermint essential oil and menthol may represent a safe, low cost and noninvasive adjuvant abortive therapy for headache pain in migraine patients. However, further high-quality clinical studies are clearly warranted to determine efficacy, safety and to establish their best treatment regimen.